Redshift As Slow-Light on Base of Frequency on Model of Galaxy GN-Z11 - Rota, Luciano M.R. (JOURNAL OF ADVANCES IN PHYSICS, 2022)
The calculation of the redshift on base of wavelength leads to the conclusion that the regression speed of some body showing a shift >1 can greatly exceed that of light. This research, taking as model the most far from us galaxy GN-z11, discovered in 2016, shows that results given on base of decreasing of frequency as consequence of slowed light-speed, could concretely solve the complex question of the redshift of bodies very distant from us. The results related to this model could be further substantially confirmed by performing an experiment briefly described here.